2007
DOI: 10.1177/0305735607085012
|View full text |Cite
|
Sign up to set email alerts
|

Young adolescents' usage of narrative functions of media music by manipulation of musical expression

Abstract: This study investigates usage and knowledge of musical narrative functions in contemporary multimedia. A group of young adolescents were given the task of adapting musical expression, using the non-verbal research tool REMUPP, to fit different visual scenes shown on a computer screen. This was accomplished by manipulating seven musical parameters: instrumentation, tempo, harmonic complexity, rhythmic complexity, register, articulation and reverb. They also answered a questionnaire giving information about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
(1 reference statement)
0
12
0
4
Order By: Relevance
“…Nyk€ anen (2008) and Nyk€ anen, Johnsson, Sirkka, and Johansson (2013) suggested that simple auralizations (analogous to visualizations) could be used as sound sketches, and similar ideas have been expressed by Jansen, € Ozcan, and Van Egmond (2011), Schifferstein and Desmet (2008), Wingstedt (2008), Wingstedt, Br€ andstr€ om, and Berg (2008), and € Ozcan and van Egmond (2008). Moussette (2012) undertook a thorough study of how to utilize sketching of haptics in interaction design.…”
Section: Sketching Sounds 23mentioning
confidence: 88%
“…Nyk€ anen (2008) and Nyk€ anen, Johnsson, Sirkka, and Johansson (2013) suggested that simple auralizations (analogous to visualizations) could be used as sound sketches, and similar ideas have been expressed by Jansen, € Ozcan, and Van Egmond (2011), Schifferstein and Desmet (2008), Wingstedt (2008), Wingstedt, Br€ andstr€ om, and Berg (2008), and € Ozcan and van Egmond (2008). Moussette (2012) undertook a thorough study of how to utilize sketching of haptics in interaction design.…”
Section: Sketching Sounds 23mentioning
confidence: 88%
“…To answer this question, Baker, Staiano, and Calvert (2011) examined the digital creations made by twenty-four African American adolescents who were attending a college preparatory summer program at Georgetown University, which is located in Washington, DC. This procedure allowed adolescents even more creative freedom than in the Wingstedt et al (2008) study. Students were taught basic fi lm editing techniques and then given a camera to take pictures about their summer experiences on campus.…”
Section: Youth Digital Communications and Digital Creationsmentioning
confidence: 99%
“…Wingstedt et al [44] describe a methodology that could be of direct relevance to the narrative side of game music evaluation, but which does not focus explicitly on emotions. Previously, they had designed a system that allows the user to adjust several features (e.g., tempo, harmonic complexity) of a piece of music in real time via a set of graphical sliders.…”
Section: Conveyance Of Narrativementioning
confidence: 99%